Latin American readings of Gramsci and the Bolivian indigenous nationalist state. Issue 1 (2nd January 2021) - Coletta, Michela; Raftopoulos, Malayna
ABSTRACT: This article engages critically with recent theories on the eclipse of Gramsci's notion of hegemony in the face of twenty-first-century practices of grassroots activism. It demonstrates how hegemony, and other concepts reworked from Gramscian thought, have been used as the theoretical basis for assimilating indigeneity into a new form of nationalism in Bolivia. The first section of this piece examines the role of Gramscian thought in the emergence of Latin American decolonial thinking, while the second section maps out its most influential Bolivian interpretations. Finally, the third section shows how these principles have played out in the MAS movement and Evo Morales' presidencies (2006–2019). This article argues that the Morales administration, by weaving concepts of Gramscian provenance such as 'motley society' and the 'apparent state' into the Plurinational principle, created a new nationalist conservatism in the form of a hegemonic indigenous state that contradicts the basic theoretical and legal premises of Plurinationality.